"CHAPTER 33. REFORESTATION AND NATURAL SUCCESSION AS TOOLS. FOR RESTORATION ON ABANDONED PASTURES. IN THE ANDES OF SOUTH ECUADOR" - AGUIRRE MENDOZA, NIKOLAY ARTURO (2011)
Ecuador is one of the global hot spots of biodiversity. Nevertheless, it faces high deforestation rates and unsustainable land use resulting in a substantial and growing amount of degraded land, which needs to be rehabilitated for productivity and biodiversity purposes. We present the results of a reforestation experiment within a gradient of three successional phases after abandonment of pastoral use. Six native species were tested against two exotics. Furthermore, we analyzed the regeneration potential from the soil seed bank and monitored the development of the diversity of woody species in the natural succession at the different sites. Our results show that dependence on natural regeneration for forest recovery cannot be an acceptable solution for forest users, due to the low speed of recovery and the insufficient species composition of the regeneration. Planted seedlings of native species are able to cope with the harsh conditions if they are selected according to their adaptation to the environmental characteristics of the respective planting sites.